Mother’s knowledge and attitude towards measles-rubella immunization status in infants - Sarza, Rahma Delvia; Ismail, Djauhar; Wahab, Abdul (BKM Public Health and Community Medicine, 2021)
Purpose: MR immunization is a key program by the Indonesian government to support global measles and rubella elimination by 2020. However, MR immunization coverage remains low in West Sumatra, particularly at Simpang Empat Health Center, West Pasaman Regency. This study aims to determine the relationship between knowledge and attitudes with MR immunization status in infants aged 12-24 months at Simpang Empat Health Center, Pasaman Regency. Methods: The research method used was observational analysis with a cross-sectional research design. Data were collected using a purposive sampling technique with a total of 112 mothers in Simpang Empat. Results: The study found that the ratio of infants aged 12–24 months without MR immunization to those with immunization was 1:1.5. Among immunized children, 67% of mothers had good knowledge, and 63% had a positive attitude. For unimmunized children, 51% of mothers had good knowledge, while 67% had a positive attitude. Bivariate and multivariate analyses showed no significant association between mothers’ knowledge (p = 0.09) or attitude (p = 0.67) and MR immunization status at Simpang Empat Health Center. Conclusion: There is no significant relationship between knowledge and attitudes of mothers with MR immunization status. Considering the variables of access to health services and access to health information, mothers with good knowledge have 3 times the opportunity to carry out MR immunization compared to mothers with poor knowledge.